The taiwan question in the emergence of a multipolar world (2019–2024) - Taiana, Francisco A. (2025)
Geopolitical analysis of the fluctuating dynamics in cross-Strait relations between the PRC and the authorities in Taipei during the profound geopolitical changes that took place in the period 2019–2024.